2019
DOI: 10.7150/thno.37397
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Model of Inflammatory Bowel Disease in IL-10-/- Transgenic Mice: Evaluation with Ultrasound Molecular Imaging

Abstract: Objective: Acute mouse models of inflammatory bowel disease (IBD) fail to mirror the chronic nature of IBD in patients. We sought to develop a chronic mouse IBD model for assessing long-term anti-inflammatory effects with ultrasound molecular imaging (USMI) by using dual P- and E-selectin targeted microbubbles (MBSelectin).Materials and Methods: Interleukin 10 deficient (IL-10-/- on a C57BL/6 genetic background; n=55) and FVB (n=16) mice were used. In IL-10-/-mice, various experimental regimens including pirox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Based on their immunomodulatory and tissue regenerative potential, mesenchymal stem cells (MSCs) have been proposed as promising candidates for the treatment of inflammatory bowel disease (IBD) 1 - 3 . There is increasing evidence that MSCs can regulate the biological activities of a variety of immune cells, such as T cells, B cells, NK cells, neutrophils and macrophages 4 . At present, the immunomodulatory mechanism of MSCs is still not fully elucidated, but it is generally believed that MSCs exert their immunosuppressive function mainly through intercellular contact and secretion of soluble factors, such as transforming growth factor-β1 (TGF-β1), hepatocyte growth factor (HGF), indoleamine 2,3-dioxygenase (IDO), nitric oxide (NO), and prostaglandin E 2 (PGE 2 ) 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on their immunomodulatory and tissue regenerative potential, mesenchymal stem cells (MSCs) have been proposed as promising candidates for the treatment of inflammatory bowel disease (IBD) 1 - 3 . There is increasing evidence that MSCs can regulate the biological activities of a variety of immune cells, such as T cells, B cells, NK cells, neutrophils and macrophages 4 . At present, the immunomodulatory mechanism of MSCs is still not fully elucidated, but it is generally believed that MSCs exert their immunosuppressive function mainly through intercellular contact and secretion of soluble factors, such as transforming growth factor-β1 (TGF-β1), hepatocyte growth factor (HGF), indoleamine 2,3-dioxygenase (IDO), nitric oxide (NO), and prostaglandin E 2 (PGE 2 ) 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…If suitable biomarkers were identified in ex vivo body fluids, it would lead to an increase in research efforts to develop point-of-care diagnostics. Here, we investigated the association between fecal MMP-9 and serum TNF-α level due to inflammation using an established IL10–/– mouse model that has been used to determine the IBD severity. , We found that these two biomolecules could be potentially used to monitor inflammation in IBD. We note that these biomarkers are also elevated in other diseases like rheumatoid arthritis and, therefore, these biomarkers cannot be used to detect IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, associated cytokines such as IL-6, IL-17, IFN-, and TNF- were proved to be modulated which suggested that NZ9000/IL-35 could be a good candidate for preventing IBD development (J. Wang et al, 2019 ). These investigations give an excellent foundation for the potential efficacy of engineered L. lactis as LBP in the treatment of IBD.…”
Section: Role Of Microbiota In the Therapy Of Ibdmentioning
confidence: 99%